Safety Leadership - Griffin, M.; Talati, Zenobia (Oxford University Press, USA, 2014)
Safety-critical environments pose a number of complex challenges for leaders. At the interpersonal level, leaders must devote their time to monitoring safety behaviors, providing feedback, setting goals, and providing rewards to improve the behaviors of their followers. At the organizational level, leaders must work to create a positive safety culture where employees feel a sense of trust in management and empowerment. In addition to managing human error, leaders need to maintain the integrity of machines and technology used in the work environment. This chapter demonstrates the positive impact of these leader behaviors on safety performance at different organizational levels. In addition, it reviews how leaders can balance the safety goals intrinsic to high reliability with goals to support a productive and proactive workforce that goes beyond compliance and actively participates in the safety process.